2016
DOI: 10.1007/s00381-016-3052-z
|View full text |Cite
|
Sign up to set email alerts
|

Reversible diffusion weighted imaging hyperintensities during the acute phase of ischemic stroke in pediatric moyamoya disease: a case report

Abstract: These findings indicate that a wide area of DWI hyperintensity during the acute phase of ischemic stroke can be reversed by appropriate treatment in pediatric moyamoya disease. To the best of our knowledge, this is the first report of reversible DWI hyperintensities over a wide cortical area during the acute phase of ischemic stroke in pediatric moyamoya disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Furthermore, there was no correlation between early reperfusion and DWI reversal 64 . Reversibility of diffusion restriction has been reported in pediatric patients with AIS, although this phenomenon has not been well characterized 65 . In a cohort of 29 children with ischemic stroke, the established adult ADC threshold of <620 × 10 –6 mm 2 /s strongly correlated with the DWI lesion in early time windows 63 .…”
Section: Imaging Selection Of Children For Endovascular Stroke Therapymentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, there was no correlation between early reperfusion and DWI reversal 64 . Reversibility of diffusion restriction has been reported in pediatric patients with AIS, although this phenomenon has not been well characterized 65 . In a cohort of 29 children with ischemic stroke, the established adult ADC threshold of <620 × 10 –6 mm 2 /s strongly correlated with the DWI lesion in early time windows 63 .…”
Section: Imaging Selection Of Children For Endovascular Stroke Therapymentioning
confidence: 87%
“…64 Reversibility of diffusion restriction has been reported in pediatric patients with AIS, although this phenomenon has not been well characterized. 65 In a cohort of 29 children with ischemic stroke, the established adult ADC threshold of <620 Â 10 -6 mm 2 /s strongly correlated with the DWI lesion in early time windows. 63 Another report of 4 children with acute stroke and MR RAPID perfusion imaging also found that ADC volume <620 Â 10 -6 mm 2 /s correlated with final DWI volume on follow-up imaging.…”
Section: Imaging Selection Of Children For Endovascular Stroke Therapymentioning
confidence: 92%
“…Since the 1990s, the diffusion weighted imaging has recognized as the best technique in early detection of strokes (21)(22)(23)(24)(25). Recently, with the technical development of MR imaging in the areas of imaging sequences and gradient coils, the amount of time required to image other areas of the body has decreased profoundly.…”
Section: Applicationsmentioning
confidence: 99%
“…However, the association between DWI lesions and the infarction core has been challenged in several recent case reports and systemic analysis of DWI reversal. [1][2][3] These reversals are usually observed in patients with small lesions, relatively higher ADC values, or rapid endovascular reperfusion. [3][4][5][6] Herein, we report a case of reversal of a large ischemic lesion on DWI with corresponding low ADC values in acute middle cerebral artery (MCA) infarction after immediate spontaneous recanalization.…”
mentioning
confidence: 99%